[In] Searching Our Mothers’ Archives - Su'ad Abdul Khabeer (African Journal of Gender and Religion (AJGR))
Black feminist scholarship provokes us to reimagine archives in creative and speculative ways and echoes everyday Black communities’ deep investment in memory that rejects the idea of African people as a people without history. I enter this discourse through Umi’s Archive is an interdisciplinary and multimedia research project that draws on my family archive to engage everyday Black women’s thought to investigate key questions of archives and power. In this article, I describe my experience curating, preserving, and presenting the archive and how that became a process of de-disciplining myself, turning to intimacy and mourning to learn from Black women by searching in my Umi’s archive.